Avaliação do potencial antileishmania dos compostos naturais isolados ácido úsnico, cumarin, quercetina e reserpina sobre as formas promastigotas e amastigotas de Leishmania Chagasi - Martins, Amely Branquinho (2008)
Leishmaniases are a complex of infectious parasitic diseases caused by species of the Leishmania genus. These diseases comprise a large spectrum of manifestations ranging from localized self-healing cutaneous lesions to fatal visceral infections. In Brazil, the visceral leishmaniasis is caused by Leishmania chagasi which affects ca. 2 million people every year with estimated 90% of cases occurring in Northeastern. Current treatments of leishmaniasis are based on first line pentavalent antimonials or other drugs like amphotericin B and pentamidine. Toxicity of those drugs, their high sideeffects, besides the high cost of treatment, difficulty for administering them and the surge of resistance are their great drawbacks. These aspects have stimulated the search for new leishmanicide agents, like the isolation and identification of natural compounds which could provide new therapeutic models for the treatment of leishmaniases. It was aimed in the present work a comparative evaluation of potentially antileishmania natural isolate compounds and their action on promastigote and amastigote forms of Leishmania chagasi by observing the cycle of this parasite in vitro. Assays were carried out with usnic acid, coumarin, quercetin, and reserpine which showed to have significant antileishmanial activity on promastigote forms of Leishmania chagasi, presenting IC50 equal to 0.0417; 1.07; 0.271 and 1.7 mM, respectively. It was possible in our experimental conditions of standardized cultivation of parasites, to establish their life cycle in vitro, by observing their metamorphosis from promastigote to mastigote. The in vitro life cycle was characterized by parasite cultivations with establishment of: 1) lag (initial), log or exponential and stationary stages of promastigotes; 2) transformation of promastigotes to intracellular amastigotes by infection of murine macrophages; this step favoured the promastigotes infectivity; and 3) amastigote isolation and transformation to promastigotes completing the cycle. Furthermore, it was also possible to establish the in vitro transformation of promastigotes in axenic amastigotes of Leishmania chagasi and its use for the evaluation of antileishmanial activity. In this case, the natural compound usnic acid exhibited antileishmanial activity against axenic amastigote forms with IC50 of 1,16 mM. It was not observed any similarity of IC50 on antileishmanial activity of usnic acid and pentamidine between the axenic amastigote and promastigote forms. This demonstrates that it is important to characterize the action of compound on each life form of the parasites. It is concluded that all assayed compounds carried out in this work had antileishmanial activity on promastigote forms, mainly, and the effect of concentration was different between promastigote, of lower IC50 values, and axenic amastigotes forms, of greater IC50 values.